Editorial - Teye, Prof. G. A. (UDS International Journal of Development, 2025)
The second issue of Volume 11 of the UDS International Journal of Development (UDSIJD) has been published. This issue has a total of 6 papers with majority (5) of the papers covering the Humanities and one, covering the Agricultural Sciences. As an international journal, the team desires to continue to work hard to publish original and credible articles to maintain standards. As such, authors are urged to always use the author’s guidelines when writing and structuring their manuscripts to avoid delays. We urge members of the university community, researchers and academics to submit manuscripts to the journal for consideration. The editorial team wishes to thank the Management of the University, contributors, reviewers and all who have supported in diverse ways to make this a success. The Editor-in-Chief Prof. G. A. Teye